A 48‐Hour Vegan Diet Challenge in Healthy Women and Men Induces a BRANCH‐Chain Amino Acid Related, Health Associated, Metabolic Signature. Issue 3 (28th December 2017) - Draper, Colleen Fogarty; Vassallo, Irene; Di Cara, Alessandro; Milone, Cristiana; Comminetti, Ornella; Monnard, Irina; Godin, Jean‐Philippe; Scherer, Max; Su, MingMing; Jia, Wei; Guiraud, Seu‐Ping; Praplan, Fabienne; et al.
Abstract : Scope: Research is limited on diet challenges to improve health. A short‐term, vegan protein diet regimen nutritionally balanced in macronutrient composition compared to an omnivorous diet is hypothesized to improve metabolic measurements of blood sugar regulation, blood lipids, and amino acid metabolism. Methods and results: This randomized, cross‐over, controlled vegan versus animal diet challenge is conducted on 21 (11 female, 10 male) healthy participants. Fasting plasma is measured during a 3 d diet intervention for clinical biochemistry and metabonomics. Intervention diet plans meet individual caloric needs. Meals are provided and supervised. Diet compliance is monitored. Conclusions: The vegan diet lowers triglycerides, insulin and homeostatic model assessment (HOMA‐IR), bile acids, elevated magnesium levels, and changed branched‐chain amino acids (BCAAs) metabolism ( p  < 0.05), potentiating insulin and blood sugar control after 48 h. Cholesterol control improves significantly in the vegan versus omnivorous diets. Plasma amino acid and magnesium concentrations positively correlate with dietary amino acids. Polyunsaturated fatty acids and dietary fiber inversely correlate with insulin, HOMA‐IR, and triglycerides. Nutritional biochemistries, BCAAs, insulin, and HOMA‐IR are impacted by sexual dimorphism. A health‐promoting, BCAA‐associated metabolic signature is produced from a short‐term, healthy, controlled, vegan diet challenge when compared with a healthy, controlled, omnivorous diet. Abstract : The vegan diet decreases plasma AA, HOMA‐IR, Chol/HDL, and bile acids while increasing Mg, with the animal diet having opposing effects. Dietary SFAs increases TGs in the animal diet; high dietary PUFA and fiber intakes from the vegan diet reduces HOMA‐IR and TGs. Dietary AA increases 11 plasma AA. Solid lines and arrows depict significant Spearman's correlations between diet and plasma variables and between plasma metabolites; dotted lines depict known associations. Biomarkers that show significant gender dimorphic responses to the diet interventions are circled.